Keunggulan Bersaing UMKM Sektor Kabupaten Nganjuk Di Era Revolusi Industri 4.0 Di Tinjau Dari Orientasi Pasar, Inovasi Produk, Dan Orientasi Kewirausahaan - Setyani, Adika Desi; Rusandy, Debby Satyo; Sumarji, Sumarji (Universitas Islam Kadiri, 2023)
This research is motivated by the level of competition in the culinary business world which is now increasingly rampant. MSMEs are competing to continue to innovate following advances in information technology and create distinct product advantages. This study aims to determine the effect of market orientation, product innovation, and entrepreneurial orientation on SMEs in Nganjuk Regency. This research is quantitative, The resource primary from questionnaires distributed to MSME actors in Nganjuk Regency. The population in this study is SMEs that fit the research criteria. The sample used was 82 respondents. The test equipment used in this study is the classical assumption test, multiple linear regression, hypothesis testing, and determination testing with the help of SPSS version 25. The conclusions are (1) There is a significant and partial effect, between market orientation and competitive advantage in centers MSMEs sleepy district. (2) There is a significant and partial influence between product innovation and competitive advantage in the MSME centers of Nganjuk Regency. (3) There is a significant and partial influence between entrepreneurial orientation and competitive advantage in the MSME centers of Nganjuk Regency. (4) There is a significant and partial influence between market orientation, product innovation, and entrepreneurial orientation with competitive advantage in the MSME centers of Nganjuk Regency.